Location Area and Premise Size of Successful Edible Bird Nest (EBN) Swiftlet Houses in Terengganu, Malaysia - Munirah Abd Rahman, Puspa Liza Ghazali, Eni Noreni Mohamad Zain, Roslida Abdul Razak, Noor Emmiey Shafieza Sazali, Mustafa Mamat (International Journal of Advanced Science and Technology, 2020)
Many entrepreneurs are very interested to start edible bird nest (EBN) swiftlet ranching. However, majority of them lack knowledge in suitable location and premise size factors for succesfull EBN swiftlet house. This study compare location and premise size in coastal, rural and urban area in Terengganu to investigate factors that play a critical role in determining the success of a swiftlet ranching venture. This study was conducted in 12 EBN swiftlet house in Terengganu namely four in coastal, rural and urban area respectively. Locations, size of premise, number of floor and number of nest were recorded. It was found that a 2800 (70x40) square feet 3-floor EBN swiftlet house from the second rural area produced the highest number of nests (273 nests), whereas the lowest number of nests harvested from the second EBN swiftlet house in urban area, that was a 3-floor 1012 (46x22) square feet of swiftlet house. Strangely, the third EBN swiftlet house from the urban area, the smallest EBN swiftlet house consisting of 1 floors and size 800 (40x20) square feet of swiftlet house produced the second highest number of nests (256 nests). There is significant correlation among production of EBN with location of swiftlet house. Location and premise size were the success factors to ensure high swiftlet population which in term contributes to higher nest production.Keywords: Location, premise size, swiftlet house, edible bird nest production, sustainable management